2005
DOI: 10.1093/aje/kwi185
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Contextual Influences on Depressive Symptoms in the Elderly

Abstract: To understand whether neighborhood contexts contribute to the onset or maintenance of mental health problems independently of individual characteristics requires the use of multilevel study designs and analytical strategies. This study used a multilevel analytical framework to examine the relation between neighborhood context and risk of depressive symptoms, using data from the New Haven component of the Established Populations for Epidemiologic Studies of the Elderly, a community-based sample of noninstitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
184
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(200 citation statements)
references
References 19 publications
(30 reference statements)
10
184
2
4
Order By: Relevance
“…This suggests that our individual-level indicators included the important ones. Our principal findings on area effects are consistent with most previous studies [38][39][40] , although two studies have reported effects of neighbourhood SES on depressive symptoms which persisted in models controlling for individual-level SES 41,42 . It has been suggested that the effects of area-level variables may reflect weaknesses of individual-level model 43 , such as missing important variables.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that our individual-level indicators included the important ones. Our principal findings on area effects are consistent with most previous studies [38][39][40] , although two studies have reported effects of neighbourhood SES on depressive symptoms which persisted in models controlling for individual-level SES 41,42 . It has been suggested that the effects of area-level variables may reflect weaknesses of individual-level model 43 , such as missing important variables.…”
Section: Discussionsupporting
confidence: 91%
“…Rather than simply measuring individual perceptions of others' stigma, we suggest that a true measure of public stigma should contextualize the aggregate environment of individual self-beliefs about stigma at a specific time and in a specific place. As scholars have suggested in a wide-ranging literature on neighborhood and school contextual effects, individual characteristics and aggregated individual characteristics at the group level may each have their own influence on social processes and outcomes (Harding 2003;Jencks and Mayer, 1990;Kubzansky et al 2005;Lauen and Gaddis 2013;Sampson, Morenoff, and GannonRowley 2002;Sharkey et al, 2012). In fact, recent work has highlighted the link between community-level prejudice and health outcomes (Blair and Brondolo 2017;Orchard and Price 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Building on this work, the neighborhood service environment, as measured by availability of various types of businesses and organizations hypothesized as favorable or unfavorable to health, has been examined for its association with health outcomes. 9,10 Researchers are beginning to assess the quality of secondary data sources with business information, [11][12][13][14] given that these data sources are increasingly being used in research with some expressing concerns about the accuracy and completeness of these data sources. 5,[15][16][17][18] Information on the completeness and accuracy of multiple data sources for ascertaining local businesses is important not only to health researchers, but also to community organizations, policy-makers, transportation planners, and others who seek to map local businesses and resources.…”
Section: Introductionmentioning
confidence: 99%